PENGARUH REVIEW BEAUTY VLOGGER DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA PRODUK SKINCARE SOMETHINC - Shally Solihah; Ani Solihat, Yayu Sri Rahayu; Djunarto Djunarto; Andry Trijumansyah (CV. Adiba Aisha Amira, 2025)
There are many factors that influence making a purchasing decision, one of which is consumers looking for information about a product through Review beauty vlogger. In this research there are two factors, namely Review beauty vlogger and product quality. This research aims to analyze the influence of Review beauty vlogger and Product quality on Purchasing Decisions. This type of research is quantitative research using Nonprobabillity Sampling techniques. With a total of 100 respondents, these respondents were those who actively watched Youtube channels and who had purchased Somethinc Skincare product. Data were collected by distribusting questionnaires and data were processed using SPSS version 29.0. Data analysis uses multiple linear regression. The results of this research data show that: (1) Beauty Vlogger Reviews (XI) have a significant influence on Purchase Decisions (Y). (2) Product quality (X2) has a significant effect on purchasing decisions (Y). The influence of Beauty Vlogger Reviews and Product Quality on Purchasing Decisions can be seen from the results of the hypothesis test which shows that H0 is rejected and H1 is accepted so that there is a positive and significant influence.